2018
DOI: 10.21595/jve.2017.19069
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of offshore wind turbine blades under the action of wind shear and fluctuating wind

Abstract: Aiming at large-scale offshore wind turbine blades, governing equations in fluid domain and motion equations in structural domain with geometric nonlinearity were built by the aid of ALE method. A three dimensional model under fluid-structure interaction (FSI) was established by using UG software and Geometry module, and numerical calculation for FSI vibration characteristics of wind turbine blades under the effects of wind shear and fluctuating wind was carried out based on ANSYS Workbench. The results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Noyes [28] used unsteady aerodynamic experiments to analyze the influence of tower shadow effect on aerodynamic loads and blade-bending moments of downwind two-blade wind turbines. Zhang [29] found that the maximum displacement and Mises stress increase with the increase of the average wind speed under the tower shadow effect. Li [30] investigated the aeroelastic coupling effect under periodic unsteady inflows, indicating that the tower shadow effect causes dramatic changes in the tilting moment, thrust force and output power when the blade rotates in front of the tower.…”
Section: Introductionmentioning
confidence: 99%
“…Noyes [28] used unsteady aerodynamic experiments to analyze the influence of tower shadow effect on aerodynamic loads and blade-bending moments of downwind two-blade wind turbines. Zhang [29] found that the maximum displacement and Mises stress increase with the increase of the average wind speed under the tower shadow effect. Li [30] investigated the aeroelastic coupling effect under periodic unsteady inflows, indicating that the tower shadow effect causes dramatic changes in the tilting moment, thrust force and output power when the blade rotates in front of the tower.…”
Section: Introductionmentioning
confidence: 99%